Hubungan Jenis Perokok dengan Pengetahuan tentang Penyakit Kanker Paru pada Siswa di SMAN 1 Wongsorejo - Andrik Hermanto; Bernadetta Germia Aridamayanti; Ulul Azmi Iswahyudi (PROFESSIONAL HEALTH JOURNAL, 2023)
Introduction: Lung cancer is the leading cause of death after breast cancer and cervical cancer. Cigarettes are the main cause of lung cancer, besides air pollution, family history and previous cancer history also affect. Method: This research is a quantitative study with a descriptive design of correlation with a cross sectional study method. The sample used was 120 respondents taken by purposive sampling technique. Results: The p-value in the Pearson Chi-Square test results is 0.000 < 0.05, so it can be concluded that there is a relationship between the type of smoker in students and knowledge of lung cancer. Conclusion: A good knowledge of the dangers of cigarettes for students can help to prevent lung cancer. Not only can active smoking be harmful to a student's health, but passive smoking can also be the cause of such lung cancer. Increasing knowledge by providing education is very necessary for students to be able to improve their health degree by not smoking and avoiding direct exposure to cigarette smoke